2017
DOI: 10.1111/hir.12186
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to using electronic evidence based literature in nursing practice: a systematised review

Abstract: There appears to be an important role for hospital management in providing nurses with enough time and access to online information while at work and also for health care librarians together with nursing leaders in providing the required training on using electronic evidence based literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
1
14
2
3
Order By: Relevance
“…In Sweden, Heiwe et al [ 13 ] identified lack of time, statistical knowledge, and research and appraisal skills as important barriers for EBP among hospital-based occupational therapists. Similar barriers have also consistently been reported in other healthcare professions, for example, physiotherapists [ 21 , 27 , 28 ], physicians [ 29 , 30 ], and nurses [ 31 ].…”
Section: Discussionsupporting
confidence: 74%
“…In Sweden, Heiwe et al [ 13 ] identified lack of time, statistical knowledge, and research and appraisal skills as important barriers for EBP among hospital-based occupational therapists. Similar barriers have also consistently been reported in other healthcare professions, for example, physiotherapists [ 21 , 27 , 28 ], physicians [ 29 , 30 ], and nurses [ 31 ].…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, the low use of online/electronic practice support resources and research databases in our results, relative to higher use of Internet search engines such as Google, suggests that rural and remote nurses are accessing non-peer-reviewed information of questionable quality to a greater extent than research-based information. Evidence suggests that the main barriers to using research literature (e.g., electronic database subscriptions) among nurses include time, skill, and access [57].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an example of a systematic review of literature published 2010–2017 in which barriers to using electronic resources is examined within nursing practice 5 . Sadoughi et al .…”
Section: In This Issue…mentioning
confidence: 99%